Tackling Environmental Problems from the Root: An Ibuanyidanda Perspective - Bisong, Peter (Studia Ecologiae et Bioethicae, 2024)
There are series of reports in the media, books, conferences, symposia, et cetera of the deplorable condition of our natural environment. This crisis afflicting the environment occasioned by increasing human activities has reached the level that, the survival of the human species itself is threatened. Urgent remedies, therefore, need to be sought for. Though, many attempts have been made to remedy the situation, unfortunately environmental crisis continues to deepen, because the root problem (defective mindset) has not yet been fully tackled. This article presents an ethic from Asouzu’s Ibuanyidanda philosophy, which sees realities as missing links and argues that this ethic can guide human actions toward environmental sustainability. What could be garnered from Asouzu’s Ibuanynidanda philosophy is that environmental problems could be traced to defective mindsets that human beings are imbued with. Thus, unlike most other environmental ethical theories that aim at controlling human actions towards the environment, Ibuanyidanda theory believes the present environmental crisis could only be resolved if the root cause (the mind) is tackled. This is because, it is better to tackle the root cause of our negative actions (mind) than to concentrate on the actions themselves. When a change of our present divisive and hegemonic mindset, is thoroughly affected as prescribed by Ibuanyidanda philosophy, environmental sustainability instead of degradation would become the byproduct of our development.